Antisite Defects and Chemical Expansion in Low‐damping, High‐magnetization Yttrium Iron Garnet Films. Issue 2 (19th December 2022) - Santiso, Jose; García, Carlos; Romanque, Cristian; Henry, Loïc; Bernier, Nicolas; Bagués, Núria; Caicedo, José Manuel; Valvidares, Manuel; Sandiumenge, Felip
Abstract: Yttrium iron garnet is widely investigated for its suitability in applications ranging from magneto‐optical and microwave devices to magnonics. However, in the few‐nanometer thickness range, epitaxial films exhibit a strong variability in magnetic behavior that hinders their implementation in technological devices. Here, direct visualization and spectroscopy of the atomic structure of a nominally stoichiometric thin film, exhibiting a small damping factor of 3.0 ⋅ 10 −4, reveals the occurrence of Y‐excess octahedral antisite defects. The two‐magnon strength is very small, Γ0 ≈10 −6 Oe, indicating a very low occurrence of scattering centers. Notably, the saturation magnetization, 4π Ms =2.10 (±0.01) kOe, is higher than the bulk value, in consistency with the suppression of magnetic moment in the minority octahedral sublattice by the observed antisite defects. Analysis of elemental concentration profiles across the substrate‐film interface suggests that the Y‐excess is originated from unbalanced cationic interdiffusion during the early growth stages. Abstract : Nanoscale epitaxial yttrium iron garnet films still pose fundamental issues regarding their interfacial behavior and impact on magnetic properties. This work shows interfacial yttrium accumulation forming octahedral antisite defects. The resulting suppression of magnetic moment from the minority sublattice results in an increased saturation magnetization. These results suggest a strong impact of unbalanced interdiffusion on magnetic behavior.